2019
DOI: 10.9734/jpri/2019/v31i630364
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Some Spirooxindole-4H-pyran Derivatives

Abstract: Aims: Isatin is a honored scaffold and one of the most favorable class of heterocyclic systems that possesses many interesting biological activities and well-tolerated in humans. Here a series of fifteen spirooxindole-4H-pyran derivatives containing both isatin and pyran moieties (ICa-ICo) will be examine for their anti-cancer activity. Study Design: Cytotoxic evaluation of some spirooxindole-4H-pyran derivatives in two cancerous cell lines.  Place and Duration of Study: Pharmaceutical Science Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Faghih and Sharp 59 found that a solution of 20% dichloromethane and 80% isopropyl alcohol (IPA), combined with a corona surface treatment, yielded good bond strength and optical transparency for affixing PMMA sheets together. While this technique is limited by the potential for microchannel collapse, another group found that filling PMMA microchannels with a hydrophobic amine-PDMS linker prior to ethanol submersion-assisted bonding prevented channel deformation, as seen in Figure 2B.…”
Section: Device Fabricationmentioning
confidence: 99%
“…Faghih and Sharp 59 found that a solution of 20% dichloromethane and 80% isopropyl alcohol (IPA), combined with a corona surface treatment, yielded good bond strength and optical transparency for affixing PMMA sheets together. While this technique is limited by the potential for microchannel collapse, another group found that filling PMMA microchannels with a hydrophobic amine-PDMS linker prior to ethanol submersion-assisted bonding prevented channel deformation, as seen in Figure 2B.…”
Section: Device Fabricationmentioning
confidence: 99%